1982
DOI: 10.1523/jneurosci.02-04-00483.1982
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of neurite growth by extracellular electric fields

Abstract: Extracellularly applied steady electric fields of 0.1 to 10 V/cm were found to have marked effects on the neurite growth of single dissociated Xenopus neurons in culture: (1) neurites facing the cathode showed accelerated growth, while the growth of those facing the anode was reduced. Neurites growing relatively perpendicular to the field axis were prompted to curve toward the cathode. (2) More neurites appeared to be initiate from the cathodal side of the cell. (3) The number of neurite-bearing neurons per cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
228
2
5

Year Published

1989
1989
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 465 publications
(254 citation statements)
references
References 20 publications
11
228
2
5
Order By: Relevance
“…It has been suggested that electrical activity might influence the morphological characteristics and functional connectivity in the nervous system during development and in neuroplastic events. In fact, electrical activity influences various neuronal properties like synthesis of neurotransmitters (Walicke et al, 1977;Ip and Zigmond, 1984) expression of neurotransmitter receptors (Lomo and Rosenthal, 1972;Zigmond and Bowers, 198 I), the rate and direction of neurite outgrowth (Borgens et al, 1981;Pate1 and Poo, 1982;Cohan and Kater, 1986) formation and pattern of synaptic connections (Changeux and Danchin, 1976;Archer et al, 1982) and sprouting at the neuromuscular junction (Brown and Ironton, 1977;Brown et al, 198 1). Receptor-mediated changes in the morphology and the activity of the neuronal growth cone have been shown to be induced by serotonin (Haydon et al, 1984) and nerve growth factor (NGF) (Connolly et al, 1987).…”
mentioning
confidence: 99%
“…It has been suggested that electrical activity might influence the morphological characteristics and functional connectivity in the nervous system during development and in neuroplastic events. In fact, electrical activity influences various neuronal properties like synthesis of neurotransmitters (Walicke et al, 1977;Ip and Zigmond, 1984) expression of neurotransmitter receptors (Lomo and Rosenthal, 1972;Zigmond and Bowers, 198 I), the rate and direction of neurite outgrowth (Borgens et al, 1981;Pate1 and Poo, 1982;Cohan and Kater, 1986) formation and pattern of synaptic connections (Changeux and Danchin, 1976;Archer et al, 1982) and sprouting at the neuromuscular junction (Brown and Ironton, 1977;Brown et al, 198 1). Receptor-mediated changes in the morphology and the activity of the neuronal growth cone have been shown to be induced by serotonin (Haydon et al, 1984) and nerve growth factor (NGF) (Connolly et al, 1987).…”
mentioning
confidence: 99%
“…Our initial studies investigated the therapeutic potential of ES in nerve regeneration following a rat facial nerve crush injury because of ES's enhancing effects on the morphological and functional properties of neurons [1][2][3][4]. In these studies, daily, low-frequency ES hastened the onset of recovery of the eye blink reflex by reducing the initial delay in sprout formation rather than by increasing the rate of axonal regeneration, indicating that ES acts primarily on events in the early stages of recovery [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Applying electrical stimulation (ES) has been shown to affect morphological and functional properties of neurons such as nerve branching, rate and orientation of neurite growth, rapid sprouting, and guidance during axon regeneration [1][2][3][4]. Therefore, ES has been explored as a therapeutic strategy for improving the outcome of peripheral nerve injury.…”
Section: Introductionmentioning
confidence: 99%
“…However, after a lag period of 30 min following the exposure to voltage gradient, the neurites facing the anode start to regress as if being repelled by the anodal electrode. Further clarification on the response of applied Direct Current (DC) voltages on single nerve fibres was shown by Hinkle et al [40] and Patel & Poo [64]. They observed that the neurites that were parallel to the field grow towards the cathode, while the ones that were perpendicular to the electric field turned in order to grow towards the cathode.…”
Section: Applied Electrical Fields For Axonal Regenerationmentioning
confidence: 96%
“…In the absence of such guidance, the axonal growth in the CNS results in a haphazard sprouting. Various researchers studying the effects of weakly applied electric fields on the innately regenerating axons have suggested that exogenously applied weak electric fields around the lesioned axons have a role to play in facilitating axonal regeneration, possibly by providing neurotropic guidance to the growing axons [6,56,57,64].…”
Section: Axonal Regeneration Through Electrical Stimulationmentioning
confidence: 99%